2022
DOI: 10.5713/ab.21.0469
|View full text |Cite
|
Sign up to set email alerts
|

Effects of medium chain triglycerides with organic acids on growth performance, fecal score, blood profiles, intestinal morphology, and nutrient digestibility in weaning pigs

Abstract: Objective: This study was conducted to evaluate the effect of medium chain triglycerides (MCT) with organic acids (OA) on growth performance, fecal score, blood profiles, intestinal morphology, and nutrient digestibility in weaning pigs.Methods: A total of 120 weaning pigs ([Yorkshire x Landrace]) x Duroc) with an average body weight (BW) of 8.00 ± 0.87 kg were assigned in five treatments considering sex and initial BW in 3 replications with 8 pigs per pen in randomized complete block design. The experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…The results imply that incorporating 0.1 g/L and 0.15 g/L concentrations of citric acid may elevate the villus-to-crypt ratio in the murine intestine, thereby augmenting digestive and absorptive functions and ameliorating the structural configuration of the intestinal tract. Consistent with previous research [8,[30][31][32], these findings propose that various organic acids, such as CA, have the potential to impact the ratio of intestinal villous-to-crypt, which in turn has a positive effect on digestion and absorption, facilitates the growth of intestinal epithelial cells, and ensures the stability of intestinal tight junctions.…”
Section: Discussionsupporting
confidence: 90%
“…The results imply that incorporating 0.1 g/L and 0.15 g/L concentrations of citric acid may elevate the villus-to-crypt ratio in the murine intestine, thereby augmenting digestive and absorptive functions and ameliorating the structural configuration of the intestinal tract. Consistent with previous research [8,[30][31][32], these findings propose that various organic acids, such as CA, have the potential to impact the ratio of intestinal villous-to-crypt, which in turn has a positive effect on digestion and absorption, facilitates the growth of intestinal epithelial cells, and ensures the stability of intestinal tight junctions.…”
Section: Discussionsupporting
confidence: 90%
“…Benzoic acid is one of the organic acids that have been reported to improve the environment of the gastrointestinal tract and growth performance [ 22 , 23 ]. Patráš et al [ 24 ] reported a tendency for N retention to improve due to 1% dietary BA inclusion.…”
Section: Discussionmentioning
confidence: 99%